Определение длины волны оптического излучения для типирования крови фотометрическим методом - Аристов А. А. Александр Александрович; Ворончихина Ю. Н. Юлия Николаевна; Гладкова Е. И. Екатерина Игоревна; Розенбаум Ю. А. Юлия Андреевна (2022, 2022)
Заглавие с экрана